Study on the temperature field change law of high speed railway subgrade in island permafrost region - Liu, Xiaohe (Frontiers in Earth Science, 2025)
To uncover the evolution pattern of the thermal state of high-speed railway subgrade in island permafrost region and to provide a basis for rational subgrade structure design, this study focuses on the island permafrost in the test section of the Riyuexia Station along the newly constructed Harbin-Yichun High-Speed Railway (HYHSR). Field ground temperature monitoring was conducted to gather data on the island permafrost’s temperature. Utilizing a fully coupled theory of permafrost water and heat that accounts for unsaturated soil seepage and heat conduction, a numerical calculation model for island permafrost subgrade was developed. This model systematically analyzes the impacts of varying excavation and replacement depths, subgrade widths, and heights on the temperature field of island permafrost. The findings indicate that: the region along the railway exhibits a significant warming and humidification trend, with the annual average temperature and precipitation growth rates in Tieli being 0.034 °C/year and 0.67 mm/year, respectively, and those in Yichun being 0.038 °C/year and 1.93 mm/year. The natural ground temperature of island permafrost is approximately −0.3 °C, classifying it as high-temperature and extremely unstable permafrost. A greater excavation and replacement depth accelerates the degradation rate of permafrost. An increase in subgrade width expands the lateral degradation range, while an increase in subgrade height delays the decline of the permafrost table. By the 30th year, the island permafrost beneath the subgrade filling areas under all working conditions has completely degraded, with the lateral degradation width of the island permafrost increasing with depth. Through model validation and comparison across multiple scenarios, the influence mechanism of subgrade structural parameters on the thermal stability of permafrost has been elucidated. The research outcomes offer theoretical foundations and technical support for subgrade design and disease prevention and control in high-speed railway construction within island permafrost region.